Screening and identification of human HPV18VLP neutralizing antibodies from women receiving HPV vaccine - Gu, Yaru; Zhang, Rui; Wang, Wenhao; Zhou, Jinrui; Liu, Bixia; Zheng, Yan; Zuo, Houyi; Du, Yexiang; Wang, Ying; Hu, Renjian; Zuo, Qianfei (Frontiers in Immunology, 2025)
Currently, the primary treatments for cervical cancer patients are surgery or chemoradiotherapy, with a lack of standardized pharmacological therapies. Here, we report the construction of a Fab fragment phage display antibody library with a capacity of 10^9, derived from peripheral blood mononuclear cells of 15 women vaccinated against HPV. Through four rounds of screening, one clone, VLP18-Fab, specifically binding to HPV18 virus-like particles (HPV18 VLP), was selected from 40 clones. Additionally, the VLP18-Fab antibody demonstrated a highly significant and dose-dependent neutralizing activity against HPV18 pseudoviruses (P < 0.0001).Moreover,following identification, the structure of the antibody-antigen binding complex was simulated using BIOVIA Discovery Studio, which included the identification of potential binding sites. Overall, this study underscores the potential of phage-displayed antibody library technology for screening neutralizing antibodies and provides valuable insights for the design of HPV vaccines based on structural studies of antigen-antibody complexes.